Glycaemic Control Impact on Renal Endpoints in Diabetic Patients on Haemodialysis - Danielle Creme; Kieran McCafferty (International Journal of Nephrology)
Objective. To identify the number of haemodialysis patients with diabetes in a large NHS Trust, their current glycaemic control, and the impact on other renal specific outcomes. Design. Retrospective, observational, cross-sectional study. Methods. Data was collected from an electronic patient management system. Glycaemic control was assessed from HbA1c results that were then further adjusted for albumin (Alb) and haemoglobin (Hb). Interdialytic weight gains were analysed from weights recorded before and after dialysis, 2 weeks before and after the most recent HbA1c date. Amputations were identified from electronic records. Results. 39% of patients had poor glycaemic control (HbA1c > 8%). Adjusted HbA1c resulted in a greater number of patients with poor control (55%). Significant correlations were found with interdialytic weight gains (P<0.02, r=0.14), predialysis sodium (P<0.0001, r=-1.9), and predialysis bicarbonate (P<0.02, r=0.12). Trends were observed with albumin and C-reactive protein. Patients with diabetes had more amputations (24 versus 2). Conclusion. Large number of diabetic patients on haemdialysis have poor glycaemic control. This may lead to higher interdialytic weight gains, larger sodium and bicarbonate shifts, increased number of amputations, and possibly increased inflammation and decreased nutritional status. Comprehensive guidelines and more accurate long-term tests for glycaemic control are needed.